Conductivity and properties of graphene filler in poly (lactic acid) for electrostatic dissipative (ESD) film: article - Husin, Nur Zakiah Hanan; Mohamed, Rahmah; Sharudin, Rahida Wati (2019)
This research was conducted to study the conductivity and properties of biodegradable PLA/Graphene composited. The PLA resin were compounded via twin screw extruder with two composition of graphene. The mixture then tested using Melt Flow Index, Fourier Transform Infrared (FTIR), Differential Scanning Calorimetry (DSC), Mechanical properties and Impedance Analyzer. It was found that melt flow index increases as amount of graphene increases and disappearance of C-H out of plane from PLA vibration frequency which is due to greater absorption of graphene molecule compare to PLA, visible at 880-900 cm-1. Addition of graphene improved tensile strength, Young’s modulus and elongation at break.